Stop aging now! : the ultimate plan for staying young and reversing the aging process - Carper, Jean. (HarperCollins, 1995)
In Stop Aging Now!, Jean Carper -- winner of the 1995 Excellence in Journalism Award from the American Aging Association (the nation's leading group of scientists investigating the biomedical aspects of aging), nationally syndicated columnist and leading authority on health and nutrition -- documents how antioxidant vitamins, minerals, herbs and food chemicals are the magic youth potions humans have been seeking for centuries.